IGNITION ON VISUALIZATION MAINTENANCE MACHINE USING CAR MICROSOFT VISUAL BASIC 6.0 - Muhammad Kara Bachri; Jalinas. Skom. MM Jalinas. Skom. MM (Jurnal Sistem Informasi, 2003)
Currently higher cost of car maintenance. Semantara with present circumstances, weare obliged to economize in all things. For treatment ignition car engine actually nottoo difficult if done alone. With the equipment already available in house, thenanyone could do such care home he is confident and convinced that he is able toperform such maintenance. It can certainly save the cost of care up to 60% car.This application is made to provide alternative care in providing information aboutthe ignition engine using computerized media so that necessary information can befound quickly. Further, the application was created with Visual Basic 6.0programming bahsa with the intention that the resulting appearance of this applicationis the user interface, in other words easily used by the various types among the users.